#1**+2 **

\(\frac{f}{r^2}+a=n+k\)

Subtract a from each side.

\(\frac{f}{r^2}=n+k-a\)

Multiply each side by r^2.

\(f=(n+k-a)\times r^2\)

Divide each side by (n+k-a).

\(\frac{f}{n+k-a}=r^2\)

And then take the square root of each side, and you get an equation equal to r.

I'll leave this last step for you to do.

Will85237
May 29, 2018

#1**+2 **

Best Answer

\(\frac{f}{r^2}+a=n+k\)

Subtract a from each side.

\(\frac{f}{r^2}=n+k-a\)

Multiply each side by r^2.

\(f=(n+k-a)\times r^2\)

Divide each side by (n+k-a).

\(\frac{f}{n+k-a}=r^2\)

And then take the square root of each side, and you get an equation equal to r.

I'll leave this last step for you to do.

Will85237
May 29, 2018